(untitled) (mathematica didactica, 2018)
In the teaching-learning-lab ‚Good Noses Mathematics‘ primary classes (grade 4) visit the university and work in heterogeneous groups on a specific mathematical topic in form of substantial learning environments that should offer different approaches and strategies to the students. The learning environments are developed and tried out in the teaching-learning-lab, followed by a further development according to a design-research-approach. Also teacher students are integrated in the developmental process, for example when absolving practical studies or when writing their BA- or MA-theses. Moreover, selected learning environments are taken up in further teacher education courses, which enlarges the design-research-approach, for example by analyzing teacher students’ work. In the contribution, exemplary, for the learning envi-ronment ‚Fibonacci Sequence‘ the developmental research of the teaching-learning-lab will be presented. The concrete research questions include for example the investigation of the understanding of the given problems, the development of strategies and the processes of argumentation. The contribution sketches the developmental process for the complete learning environment, then putting specific design principles as well as design processes into concrete terms for the introductory unit and a combinatorial unit.